Distance education in the context of professional and technological education: considerations in pandemic times (Research, Society and Development, 2020)
Considering the pandemic COVID-19 currently plaguing the world this article aims to understand the definitions and fundamentals of Distance Education (DE), with the purpose of examining the legal basis and the adoption of distance learning at the Federal Institute of Education, Science and Technology of Amazonas (IFAM) - Campus Parintins. For this purpose, based on a qualitative approach, the bibliographic type is divided into 03 (three) parts: a) it presents the methodological procedures; b) discusses the concepts and regulatory documents of distance education in Brazil; c) deals with the legislation and the adoption of distance learning at IFAM - Campus Parintins. It is concluded that the current scenario of Pandemic provided the resumption of the debate and the countless challenges and the presence of resistances that permeate DE in the country, especially in the federal education network that deals with Professional and Technological Education. Still, this moment has led to reflexive advances that foster the immediate need to promote conditions so that this modality can in fact come to be in the country to overcome the post-pandemic challenges of COVID-19.